Innovative converged service and its adoption, use and diffusion: a holistic approach to diffusion of innovations, combining adoption-diffusion and use-diffusion paradigms - Motohashi, Kazuyuki; Lee, Deog-Ro; Sawng, Yeong-Wha; Kim, Seung-Ho (Journal of Business Economics and Management, 2012)
This study takes a holistic approach to understanding the diffusion of IPTV services by combining the adoption-diffusion model and the use-diffusion model of innovation. IPTV service, a leading converged application that couples media content with telecom services, was recently launched commercially in Korea. We created a structural model of adoption-diffusion, using the perceived ease-of-use and usefulness of TAM (Technology Acceptance Model) as mediating variables, and a structural model of usediffusion, with the rate of use and the variety of use as mediating variables. To empirically analyze these models, non-users of IPTV were surveyed using the adoptiondiffusion model to identify factors influencing their intention to subscribe to the service. Meanwhile, users of IPTV were surveyed using the use-diffusion model to determine the factors that influence their satisfaction with the service and their intention to re-use it. Under the adoption-diffusion model, we found that trialability, household innovativeness and perceived risk were the determinants of user satisfaction with IPTV, and perceived ease-of-use, the mediating factor. Under the use-diffusion model, complementarity and communication were shown to be the determinants of users’ satisfaction with IPTV, and variety of use, the mediating factor. We also found that consumers’ intentions to re-use IPTV was strongly influenced by its relative advantages and perceived risks.